Morfoquantitative and ultrastructural analysis of blood and lymph vessels in the first molars and premolars periodontal ligament - M. V. Khertek; S. V. Logvinov (Бюллетень сибирской медицины, 2011)
Morfoquantitative and ultrastructural analysis of the specific volumes of blood and lymph vessels in the periodontal first molars and premolars with different surfaces (medial, distal, buccal, and palatal) and at different levels of the roots are studied. It was noted that at physiological pressure on the molars and premolars, the specific volume of the investigated values are different. Throughout the root of the observed two zones of compression and expansion of periodontal. Depending on these areas of blood and lymphatic vessels was significantly different.